2022
DOI: 10.3389/fgeed.2021.799722
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Recombinant AAV in Precise Genome Editing

Abstract: The replication-defective, non-pathogenic, nearly ubiquitous single-stranded adeno-associated viruses (AAVs) have gained importance since their discovery about 50 years ago. Their unique life cycle and virus-cell interactions have led to the development of recombinant AAVs as ideal genetic medicine tools that have evolved into effective commercialized gene therapies. A distinctive property of AAVs is their ability to edit the genome precisely. In contrast to all current genome editing platforms, AAV exclusivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 189 publications
(262 reference statements)
0
21
0
Order By: Relevance
“…For example, D’Halluin et al [ 32 ] inserted multiple trait genes, 4-hydroxyphenylpyruvate dioxygenase ( hppd ) and modified enol-pyruvylshikimate-3-phosphate synthase genes ( epsps ) into cotton using meganucleases to enhance its herbicide tolerance. Although meganucleases have been successfully applied for targeted gene editing in the plant, they have a few limitations, such as the low catalytic activity of the enzyme, prone to sequence degeneracy, and the lack of mature DNA binding structure, which hinders their wide applications [ 33 , 34 ].…”
Section: Genome Editing Technologiesmentioning
confidence: 99%
“…For example, D’Halluin et al [ 32 ] inserted multiple trait genes, 4-hydroxyphenylpyruvate dioxygenase ( hppd ) and modified enol-pyruvylshikimate-3-phosphate synthase genes ( epsps ) into cotton using meganucleases to enhance its herbicide tolerance. Although meganucleases have been successfully applied for targeted gene editing in the plant, they have a few limitations, such as the low catalytic activity of the enzyme, prone to sequence degeneracy, and the lack of mature DNA binding structure, which hinders their wide applications [ 33 , 34 ].…”
Section: Genome Editing Technologiesmentioning
confidence: 99%
“…This was understood to be the possible result of the ITR sequence itself as it was previously found that WT-ITR containing constructs have repressed gene expression as opposed to those without ITR sequences. This is because AAV ITRs can bind to the double-strand break pathway protein ataxia-telangiectasia mutated (ATM), which can repress gene expression directly ( Bijlani et al, 2022 ). Additionally, the activation of the ATM due to the presence of ITRs can induce cell cycle arrest and apoptosis ( Pusapati et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although meganucleases have been successfully applied for targeted gene editing in the plant, they have a few limitations, such as the low catalytic activity of the enzyme, prone to sequence degeneracy, and the lack of mature DNA binding structure that hinders their wide applications [28,29].…”
Section: Genome Editing Technologiesmentioning
confidence: 99%